Impaired lymphocyte trafficking in mice deficient in the kinase activity of PKN1 - Rana Mashud (Nature Portfolio, 2017)
Abstract Knock-in mice lacking PKN1 kinase activity were generated by introducing a T778A point mutation in the catalytic domain. PKN1[T778A] mutant mice developed to adulthood without apparent external abnormalities, but exhibited lower T and B lymphocyte counts in the peripheral blood than those of wild-type (WT) mice. T and B cell development proceeded in an apparently normal fashion in bone marrow and thymus of PKN1[T778A] mice, however, the number of T and B cell counts were significantly higher in the lymph nodes and spleen of mutant mice in those of WT mice. After transfusion into WT recipients, EGFP-labelled PKN1[T778A] donor lymphocytes were significantly less abundant in the peripheral circulation and more abundant in the spleen and lymph nodes of recipient mice compared with EGFP-labelled WT donor lymphocytes, likely reflecting lymphocyte sequestration in the spleen and lymph nodes in a cell-autonomous fashion. PKN1[T778A] lymphocytes showed significantly lower chemotaxis towards chemokines and sphingosine 1-phosphate (S1P) than WT cells in vitro. The biggest migration defect was observed in response to S1P, which is essential for lymphocyte egress from secondary lymphoid organs. These results reveal a novel role of PKN1 in lymphocyte migration and localization.